Three Distinct Types of Microautophagy Based on Membrane Dynamics and Molecular Machineries - Oku, Masahide; Sakai, Yasuyoshi (BioEssays, 2018)
Microautophagy is originally defined as lysosomal (vacuolar) membrane dynamics to directly enwrap and transport cytosolic components into the lumen of the lytic organelle. Molecular details of microautophagy had remained unknown until genetic studies in yeast identified a set of proteins required for the process. Subsequent studies with other experimental model organisms resulted in a series of discoveries that accompanied an expansion of the definition of microautophagy to also encompass endosomal membrane dynamics. These findings, however, still impose puzzling, non‐integrated images as to the molecular mechanism of microautophagy. By reviewing recent studies on microautophagy in various experimental systems, we propose the classification of microautophagy into three types, as the basis for developing a comprehensive view of the process. Microautophagy represents intracellular transport pathways of cytosolic components including organelles into the lysosome (vacuole) through deformation of the lysosomal or endosomal membrane. A classification of microautophagy into three types based on the site and morphology of the membrane deformation is proposed, referring to molecular machineries elucidated to date for each type.